2017
DOI: 10.1002/2017ja024772
|View full text |Cite
|
Sign up to set email alerts
|

Flows, Fields, and Forces in the Mars‐Solar Wind Interaction

Abstract: We utilize suprathermal ion and magnetic field measurements from the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission, organized by the upstream magnetic field, to investigate the morphology and variability of flows, fields, and forces in the Mars‐solar wind interaction. We employ a combination of case studies and statistical investigations to characterize the interaction in both quasi‐parallel and quasi‐perpendicular regions and under high and low solar wind Mach number conditions. For the first time, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
169
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 93 publications
(182 citation statements)
references
References 74 publications
(104 reference statements)
12
169
1
Order By: Relevance
“…The pressure gradient force in the Z direction is negligible near the equatorial plane. The ion pressure gradient force predicted by the model is consistent with that derived from MAVEN plasma observations (Halekas et al, ).…”
Section: Simulation Resultssupporting
confidence: 84%
“…The pressure gradient force in the Z direction is negligible near the equatorial plane. The ion pressure gradient force predicted by the model is consistent with that derived from MAVEN plasma observations (Halekas et al, ).…”
Section: Simulation Resultssupporting
confidence: 84%
“…We obtain transverse wave occurrence rates of 0.32% on the dawnside and 0.55% on the duskside from the data obtained at altitudes below 3,000 km in the nominal magnetosheath region. We note that higher proton temperature anisotropy is observed by SWIA in the quasi‐perpendicular magnetosheath (Halekas et al, ), and we obtained similar results from STATIC data (not shown).…”
Section: Statistical Resultssupporting
confidence: 89%
“…Reducing this threshold leads to more positive events but at the expense of an increased risk of detecting random variations that are not MHs. The backstreaming ions move sunward in the solar wind frame with velocities in the order of a few Alfvén speed and interact with the incident solar wind, driving nonlinear ion-ion instabilities that lead to generation of ultralow frequency waves (Gary et al, 1981;Gary, 1993;Hoppe & Russell, 1983;Halekas, Brain, et al, 2017;Mazelle et al, 1991). Criterion 3 eliminates step-like events, which commonly occur during shock crossings, foreshock compressional boundaries, and Short Large Amplitude Magnetic Structures Omidi et al, 2009;Schwartz & Burgess, 1991).…”
Section: Event Identificationmentioning
confidence: 99%